2005
DOI: 10.1152/ajprenal.00464.2004
|View full text |Cite
|
Sign up to set email alerts
|

NH2-terminal heterogeneity in the KCC3 K+-Cl cotransporter

Abstract: The SLC12A6 gene encoding the K(+)-Cl(-) cotransporter KCC3 is expressed in multiple tissues, including kidney. Here, we report the molecular characterization of several NH(2)-terminal isoforms of human and mouse KCC3, along with intrarenal localization and functional characterization in Xenopus laevis oocytes. Two major isoforms, KCC3a and KCC3b, are generated by transcriptional initiation 5' of two distinct first coding exons. Northern blot analysis of mouse tissues indicates that KCC3b expression is particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 63 publications
2
83
0
1
Order By: Relevance
“…The following cDNA clones of the SLC12A family used in this study were previously reported: NCC (3), NKCC1 (9), NKCC2 (3), KCC1 and KCC4 (17), KCC2b (24), KCC3a and KCC3b (18). KCC2a (26) was obtained by cutting and pasting KCC2 exon 1a amplified from the human fetal brain cDNA library in a process similar to that described above.…”
Section: Clones Cloning and Sequencingmentioning
confidence: 99%
“…The following cDNA clones of the SLC12A family used in this study were previously reported: NCC (3), NKCC1 (9), NKCC2 (3), KCC1 and KCC4 (17), KCC2b (24), KCC3a and KCC3b (18). KCC2a (26) was obtained by cutting and pasting KCC2 exon 1a amplified from the human fetal brain cDNA library in a process similar to that described above.…”
Section: Clones Cloning and Sequencingmentioning
confidence: 99%
“…Initially, two first exons denoted by SLC12A6-1 and SLC12A6-2 (formerly KCC3a and KCC3b), which are under the control of separate promoters (Di Fulvio et al, 2001;Mercado et al, 2004), have been described where the transcript possessing alternative exon 1a is predominantly expressed in brain. So far, six alternative transcripts have been identified for SLC12A6 (Mercado et al, 2005). All transcripts except for SLC12A6-2, are regulated by the same promoter.…”
Section: Introductionmentioning
confidence: 99%
“…Erythroid function and differentiation (30), cancer cell growth and invasiveness (8,57,58), arterial blood pressure regulation (54), and neuronal excitability (23,33,53) are some of the important roles of these membrane proteins. At the renal level, KCC3 is located in the basolateral membranes of the proximal tubules (PT) (40), while KCC4 is expressed in proximal tubules, in the thick ascending limb of Henle's loop (TALH) (35), and in ␣-intercalated cells of the collecting duct (CD) (6,35). In these zones of the nephron, KCC3 and KCC4 are involved in processes such as glucose and salt reabsorption and acid-base homeostasis (6,35).…”
Section: Spak; Wnk4; Xenopus Oocytes; Hek-293 Cells the Kmentioning
confidence: 99%
“…In these zones of the nephron, KCC3 and KCC4 are involved in processes such as glucose and salt reabsorption and acid-base homeostasis (6,35). It is known that KCCs are activated due to an increase in [Cl Ϫ ] i or by cell swelling (39,40,60). This process is related to protein dephosphorylation, and its purpose is to reduce the [Cl Ϫ ] i or mediate the regulatory volume decrease (RVD) (1,14,17).…”
Section: Spak; Wnk4; Xenopus Oocytes; Hek-293 Cells the Kmentioning
confidence: 99%